PENGEMBANGAN MEDIA PEMBELAJARAN AUDIOVISUAL BERBASIS ENTERTAINMENT PADA MATA KULIAH PENGANTAR AKUNTANSI - Hasbiy, Khoirul Umam (Jurnal Ilmiah Mahasiswa FEB, 2013)
Purpose of this study was to find empirical evidence of differences in the understanding of the basic concepts of accounting between students who received audiovisual learning method based on entertainment. Against students who do not received audiovisual learning method based on entertainment. The basic concept of accounting in this study limited to accounting cycle for a service company located in the course Introduction of Accounting. The research data is secondary data and analyzed using Independent Sample T-Test. The result showed that there was no difference in the level of understanding of the basic concepts of accounting between students who received audiovisual learning method based on entertainment. Against students who do not received audiovisual learning method based on entertainment. Keywords: theacing methods, instructional media, audiovisual, basic concepts of accounting.